Embodied choices bypass narratives under radical uncertainty. (8th May 2023) - Cañal-Bruland, Rouwen; Raab, Markus
Abstract: Johnson et al. suggest that we rely on narratives to make choices under radical uncertainty. We argue that in its current version Conviction Narrative Theory (CNT) does not account for embodied, direct sensorimotor influences on choices under radical uncertainty that may bypass narratives, particularly in highly time-constrained situations. We therefore suggest to extend CNT by an embodied choice perspective.